TEACHING ENGLISH GRAMMAR THROUGH PERSON BASED ASPECTS: APPLYING NEW TECHNOLOGIES WHILE TEACHING ENGLISH TO INDIVIDUALS - Xoliyeva, Guljahon (Educational Research in Universal Sciences, 2023)
This article discusses the effectiveness of a person-oriented approach in teaching English grammar to students. The traditional way of teaching grammar focused on rules and structures, which often caused students to lose interest and motivation in learning the language. In contrast, a person-oriented approach emphasizes the use of grammar structures in context and personalizes the language learning experience to suit the individual learner’s needs, interests, and learning style. This article explores the theoretical foundations of the person-oriented approach and discusses practical strategies that teachers can use to implement this approach.